Proceedings of the 2018 SIAM International Conference on Data Mining 2018
DOI: 10.1137/1.9781611975321.54
|View full text |Cite
|
Sign up to set email alerts
|

ALE: Additive Latent Effect Models for Grade Prediction

Abstract: The past decade has seen a growth in the development and deployment of educational technologies for assisting college-going students in choosing majors, selecting courses and acquiring feedback based on past academic performance. Grade prediction methods seek to estimate a grade that a student may achieve in a course that she may take in the future (e.g., next term). Accurate and timely prediction of students' academic grades is important for developing effective degree planners and early warning systems, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 13 publications
0
15
1
Order By: Relevance
“…Their results showed that both proposed approaches outperformed existing traditional methods, and course-recommendations based on regression achieved the best results compared to (CSMF) and linear regression. (Ren et al, 2018) proposed student grade prediction model based on the Additive Latent Effect (ALE) within the framework of matrix factorization (MF) that focused on outsourced factors rather than data associated with courses and students. The dataset was obtained from George Mason University and covered the period of Fall 2009 to Spring 2016.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Their results showed that both proposed approaches outperformed existing traditional methods, and course-recommendations based on regression achieved the best results compared to (CSMF) and linear regression. (Ren et al, 2018) proposed student grade prediction model based on the Additive Latent Effect (ALE) within the framework of matrix factorization (MF) that focused on outsourced factors rather than data associated with courses and students. The dataset was obtained from George Mason University and covered the period of Fall 2009 to Spring 2016.…”
Section: Related Workmentioning
confidence: 99%
“…Machine learning was also utilized to build a recommended system that used matrix factorization and linear regression model for grade prediction (Polyzou and Karypis, 2016). Additive latent affect (ALE) along with matrix factorization (MF) were used to build a student grade prediction model (Ren et al, 2018). In (Acharya and Sinha, 2014), authors have introduced students' predictions of students' performance using machine learning techniques by studying a set of attributes.…”
Section: Introductionmentioning
confidence: 99%
“…However, grade predictions were less plausible when a student-coursespecific approach was applied. Other works incorporated additive latent effect models (i.e., ALE) within matrix factorization methods to calculate future course grades for the next terms [41]. The proposed ALE models incorporate four factors related to instructors, student academic level, student interest, and knowledge to predict future grades.…”
Section: B Approaches To Predicting Student Performancementioning
confidence: 99%
“…• Single unsupervised learning model: use of only the self-organizing map for multi-label classification. [11], [27], [41], [43], [45], [50], [51]) and their Research Gaps (denoted as RG).…”
Section: No Yesmentioning
confidence: 99%
“…Within a course, achievementoriented learners can often be seen maximizing assessment grades while mastery-oriented learners may undertake more practices and review activities. As learners can make use of the flexibility granted in tertiary education programmes to achieve these goals, models developed for learning analytics can analyze historical records to help learners understand whether they would successfully navigate the programme after deviating from the rec-Chapter 2: Review of Data Mining Approaches for Identifying Learning Behaviors ommended curriculum [26]. While there are many benefits to employ learning analytics to aid learners, it remains debatable if learners should have access to such information as learners may also be discouraged from pursuing their learning if these models constantly provide negative feedback [27,28].…”
Section: Stakeholders For Learning Analyticsmentioning
confidence: 99%